PERHITUNGAN GAS IN PLACE DAN RECOVERY FACTOR PADA LAPANGAN CBM SUMUR X - Yusraida Khairani Dalimunthe; Def Marshal; Ratnayu Sitaresmi (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2019)
The Coal Bed Methane well X is a field developed by company A where 5 CBM test wells have been drilled. This CBM field development in 2004 by drilling wells to a depth of 3000ft, then in 2006 drilling was carried out for three test wells with an average depth of 3000ft. The research conducted at LEMIGAS aims to calculate coalbed methane reservoir reserves, calculation of reserves per seam, recovery factor, from each coal sample. The volumetric method is used in this research to calculate the methane gas reserves and Langmuir curve analysis is used to calculate the recovery factor. The target of this research is the CBM field in well X, where the well has 3 seams, namely seam-2, seam-3, and seam-4. In addition to calculating the value of methane gas reserves for each well, the methane gas reserves for each seam are also calculated. From the results of the calculation, it can be concluded that the largest value of gas in place is on seam 4 which is 573.2 MMscf and the smallest is on seam 2 which is 176.1 MMscf, then the largest recovery factor value is owned by seam 3 which is 91%.